(untitled) (Research, Society and Development, 2021)
Multiprofessional residencies in health are professional qualification programs that allow the integration of students with professionals from different areas by working in fields of practice, stimulating reflective, critical, humanistic and holistic thinking. In multi-professional residencies, the pharmacist may be one of the members that make up the team and must participate in management, drug and clinical pharmacotechnics, as well as in critical and highly complex environments, highlighting the essential practice in hospital pharmaceutical care. Given the above, this article aims to report the experiences of a pharmacist resident in a multidisciplinary program focused on comprehensive care in Orthopedics and Traumatology, held at a Regional Hospital in the Lower Amazon region, city of Santarém. During the residency experience, the pharmacist can perform the pharmaceutical clinic as well as manage and deal with the various daily situations of a hospital, having the opportunity to monitor and build a therapeutic plan that follows the patient’s evolution throughout their stay in the hospital. It is observed that the resident is often exposed to different cases, having support and support to overcome their insecurities, having a direct and decisive contact in the clinical treatment of the patient, being an active member of the hospital team, finding a fertile environment in the residence. learning and specialization.